The Polysaccharide Capsule of Streptococcus pneumonia Partially Impedes MyD88-Mediated Immunity during Pneumonia in Mice - de Vos, Alex F. (PLoS One, 2015)
Toll-like receptors (TLR) and the downstream adaptor protein MyD88 are considered crucial for protective immunity during bacterial infections. Streptococcus (S.) pneumoniae is a human respiratory pathogen and a large majority of clinical pneumococcal isolates expresses an external polysaccharide capsule. We here sought to determine the role of pneumococcal capsule in MyD88-mediated antibacterial defense during S. pneumonia pneumonia. Wild type (WT) and Myd88(-/-) mice were inoculated intranasally with serotype 2 S. pneumoniae D39 or with an isogenic capsule locus deletion mutant (D39∆cps), and analysed for bacterial outgrowth and inflammatory responses in the lung. As compared to WT mice, Myd88(-/-) mice infected with D39 demonstrated a modestly impaired bacterial clearance accompanied by decreased inflammatory responses in the lung. Strikingly, while WT mice rapidly cleared D39∆cps, Myd88(-/-) mice showed 10(5)-fold higher bacterial burdens in their lungs and dissemination to blood 24 hours after infection. These data suggest that the pneumococcal capsule impairs recognition of TLR ligands expressed by S. pneumoniae and thereby partially impedes MyD88-mediated antibacterial defense.